Government and Social Media: A Case Study of 31 Informational World Cities. - (:unkn) unknown (IEEE, 2014)
Social media platforms are increasingly being used by governments to foster user interaction. Particularly in cities with enhanced ICT infrastructures (i.e., Informational World Cities) and high internet penetration rates, social media platforms are valuable tools for reaching high numbers of citizens. This empirical investigation of 31 Informational World Cities will provide an overview of social media services used for governmental purposes, of their popularity among governments, and of their usage intensity in broadcasting information online.
Keywords: Information; Informationstechnologie; Kommunikationstechnologie; Großstadt; Verwaltung; Kommunikation; Globalisierung; World City; Metropole; Social media; Soziales Netzwerk; Stadtverwaltung; Mediennutzung; Smartphone; Städtevergleich; Internationaler Vergleich